Cyber-diplomacy: the making of an international society in the digital age - Barrinha, André (2017)
Cyberspace has become a major locus and focus of international relations. Most global powers have now streamlined cyber issues into their foreign policies, adopting cyber strategies and appointing designated diplomats to pursue these strategic objectives. This article proposes to explore the concept of cyber-diplomacy, by analysing its evolution and linking it to the broader discussions of diplomacy as a fundamental institution of international society, as defined by the English School of International Relations. It argues that cyber-diplomacy is an emerging international practice that is attempting to construct a cyber-international society, bridging the national interests of states with world society dynamics – the predominant realm in which cyberspace has evolved in the last four decades.